A qualitative meta-synthesis for a theory of interfaith/interreligious learning through dialogue - Elizabeth M. Pope; Nadira K. Charaniya; Jane West Walsh (Adult Education Research Conference, 2021)
Interfaith/interreligious (IF/IR) dialogue offers a context through which individuals within various religious communities can learn from and with each other. There are unique aspects to this learning environment. First, learning through conversation. Second, learning through conversation about a difficult topic. And third, learning from and with a religious other. To best understand what learning through IF/IR dialogue is, researchers would benefit from a nuanced understanding of the complexities of the learning environment and the participants within it. In this qualitative meta-synthesis, we examine current research on IF/IR dialogue to outline a theory of dialogical IF/IR learning.
Keywords: Interfaith dialogue; interreligious dialogue; adult learning; qualitative meta-synthesis; communicative learning.